"Read for Pleasure and Learn Hebrew, Too!" - Lubetski, Edith (Judaica Librarianship, 1993)
When I attended an Association of Jewish Libraries/New York Metropolitan Area Day School Workshop at the Yeshiva of Flatbush in 1987, Mrs. Aviva Lapide, the librarian of the Yeshiva's Elementary School, showed a page listing one child's recreational Hebrew reading achievement from fourth through eighth grade. The grand total was 32,600 pages. Incredible, you say. I thought so, too. But it was true. The documentation-the titles of books the child had read and the number of pages of each volume-lay in front of us in black and white.